EFFECT OF E-FILING SOCIALIZATION ON TAX COMPLIANCE WITH E-FILING UNDERSTANDING AS AN INTERVENING VARIABLE (CASE STUDY OF INDIVIDUAL TAXPAYERS OF EMPLOYEES REGISTERED ON KPP PRATAMA PURWAKARTA) - Kiki Ratnasari; Asep Kurniawan; Asri Suangga (Journal of Taxation Analysis and Review, 2019)
This study aims to determine the effect of e-filing socialization on tax compliance. The study also aims to examine the effect of the understanding that acts as an intervening variable in the relationship between the socialization of e-filing on tax compliance. This research was conducted with a purposive sampling method that is included in the non-probability sampling with a sample of 80 respondents from individual taxpayers of employees registered on KPP Purwakarta. The data used are primary data through questionnaires, which contain respondents answers. Path Analysis is used to test the effect of intervening. The results of the study are E-Filing Socialization has positive effect on the understanding of e-filing, E-Filing socialization has positive effect on tax compliance, E-Filing Understanding has positive effect on tax compliance, e-Filing socialization has positive effect on tax compliance through e–filing understanding